Stochastic scattering in Cen A radio lobes - Sydorenko, M.V.; Marchenko, V.V.; Sushchov, O.B.; Kobzar, O.O. (Advances in Astronomy and Space Physics, 2013)
The results of direct numerical modelling of the cosmic ray acceleration in strongly excited turbulence, where quasi-linear theory is non-applicable, are presented. We model turbulent plasma by a set of randomly propagated Alfvén waves with Kolmogorov spectrum of magnetic field fluctuations. The influence of stochastic scattering in Cen A radio lobes on correlation of the ultra high energy cosmic rays (UHECR) events registered by Auger observatory with Cen A is studied. Typical radio lobe regions, which UHECR of different chemical composition are supposed to come from, are estimated by applying numerical modelling of UHECR scattering with Fermi II mechanism in the turbulent regions.